Acceleration of Lung Regeneration by Platelet-Rich Plasma Extract through the Low-Density Lipoprotein Receptor–Related Protein 5–Tie2 Pathway - Mammoto, Tadanori (Am J Respir Cell Mol Biol, 2016)
Angiogenesis, the growth of new blood vessels, plays a key role in organ development, homeostasis, and regeneration. The cooperation of multiple angiogenic factors, rather than a single factor, is required for physiological angiogenesis. Recently, we have reported that soluble platelet-rich plasma (PRP) extract, which contains abundant angiopoietin-1 and multiple other angiogenic factors, stimulates angiogenesis and maintains vascular integrity in vitro and in vivo. In this report, we have demonstrated that mouse PRP extract increases phosphorylation levels of the Wnt coreceptor low-density lipoprotein receptor–related protein 5 (LRP5) and thereby activates angiogenic factor receptor Tie2 in endothelial cells (ECs) and accelerates EC sprouting and lung epithelial cell budding in vitro. PRP extract also increases phosphorylation levels of Tie2 in the mouse lungs and accelerates compensatory lung growth and recovery of exercise capacity after unilateral pneumonectomy in mice, whereas soluble Tie2 receptor or Lrp5 knockdown attenuates the effects of PRP extract. Because human PRP extract is generated from autologous peripheral blood and can be stored at −80°C, our findings may lead to the development of novel therapeutic interventions for various angiogenesis-related lung diseases and to the improvement of strategies for lung regeneration.